Japan’s Balancing Act: Assessing Japan’s Foreign Policy towards Myanmar in the Emerging Indo-Pacific Era - Htwe, Thaingi Khin (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2021)
Prime Minister Abe officially introduced the FOIP in 2016 at the TICAD VI in Kenya aiming to preserve the RBO against increasing challenges to the vital interests of Japan. Because of Myanmar's geostrategic location, democratization, and rich natural resources, Myanmar became an important country in fostering Japan's FOIP. In this context, this paper aims to examine Japan’s foreign policy towards Myanmar in the emerging Indo-Pacific era. This paper is mainly focused on Japan’s balancing strategy in Indo-Pacific, the significance of Myanmar in Japan’s FOIP, and the foreign policy tools of Japan in Myanmar. The paper finds that Japan rapproach Myanmar by using significant 3Ds (diplomatic engagement, defense cooperation, and development assistance) in the emerging Indo-Pacific era. Japan’s foreign policy readjustment towards Myanmar in the emerging Indo-Pacific era can be interpreted as one of Japan’s limited hard balancing strategies against China.